Factors Affecting Employment In Jakarta Indonesia After Transition From Education To The World Of Work - Basuki*, Agus Tri; Mulyasari, Melita Mesti (Universitas Syiah Kuala, 2024)
This study aims to analyze the effect of the number of labor force, gross regional domestic product, capital expenditure, and foreign investment on employment in DKI Jakarta Province. The method used in this study is the Error Correction Model (ECM). The data used in this study is time series data for the period 1990-2021. The results showed that in the long and short term the number of labor force, gross regional domestic product, and capital expenditure had a positive and significant effect on employment in DKI Jakarta Province. Meanwhile, foreign investment (FDI) has no influence on the absorption of labor in DKI Jakarta Province. The DKI Jakarta government must be selective and re-evaluate the existence of foreign investors because the results of this study show that foreign investment does not contribute to employment. This will hinder the alleviation of the problem of poverty, due to the insurmountable problem of unemployment in DKI Jakarta. The DKI Jakarta government must pay serious attention to the current dynamics of industrial supply and demand, so handling transitions from school to work requires innovation and collaboration that creates selected programs that are able to adapt quickly to changes in the world of work.